2016
DOI: 10.1016/j.bmhimx.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Enfermedad de Kawasaki en un hospital pediátrico en México

Abstract: There were no important differences between classic and incomplete presentations. The incidence of cardiac alterations is less than previously reported in Mexico, but similar to that of other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
0
3
1
17
Order By: Relevance
“…Of these, only the one that received glucocorticoids presented a positive Harada score. Furthermore, 50% of the patients in this series presented echocardiography alterations, percentage higher than the 32% reported by Sotelo-Cruz 2 , the 29.4% reported by García-Rodríguez et al 11 , and the 35% reported by Surjit et al 22 However, it was similar to the 54% reported by Gil-Veloz et al 3 Our results may have been influenced by the characteristics of the patients in our series since there is female predominance, the median age is 2.1 years (lower than that reported in other series), 2,3,20 and there is a high frequency of atypical manifestations.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Of these, only the one that received glucocorticoids presented a positive Harada score. Furthermore, 50% of the patients in this series presented echocardiography alterations, percentage higher than the 32% reported by Sotelo-Cruz 2 , the 29.4% reported by García-Rodríguez et al 11 , and the 35% reported by Surjit et al 22 However, it was similar to the 54% reported by Gil-Veloz et al 3 Our results may have been influenced by the characteristics of the patients in our series since there is female predominance, the median age is 2.1 years (lower than that reported in other series), 2,3,20 and there is a high frequency of atypical manifestations.…”
Section: Discussioncontrasting
confidence: 54%
“…Regarding clinical behavior, all patients met the criteria to define complete KD, similar to that found in the most extensive series published in Mexico 2,6,11 . Similarly, all the patients presented atypical manifestations, a higher proportion than that reported in other series 2,3,6,9,20,21 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Epidemiologic studies are rare in most European countries, and the incidence of KD has been reported as less than 17.6 per 100,000 less than 5-year-olds [20], remaining stationary without significant increases or decreases as in North America [4,21,22]. In Latin America, no systematic epidemiological study of KD has been performed in each country, although the incidence of KD has been reported sporadically in several countries [23,24]. The recently founded Latin American Kawasaki Disease Network (REKAMLATINA) is expected to improve the understanding of KD epidemiology in Latin America.…”
Section: Global Incidence Of Kdmentioning
confidence: 99%
“…La falta de estudios de esta enfermedad en Latinoamérica y Panamá limita el conocimiento que se tiene de ella y el comportamiento en nuestra población. Los resultados de este estudio arrojan que la EK en Panamá se comporta de forma similar en varios aspectos a lo ya reportado en otras latitudes, como la edad promedio de 29 meses, la que es similar a lo reportado en poblaciones latinoamericanas 6 . También se evidenció una frecuencia 2,6 veces mayor en pacientes bajo 3 años de edad y en forma similar con lo encontrado en otros países, se observó un predominio del sexo masculino independientemente de la edad 6,7 .…”
Section: Discussionunclassified